Chemical and nutritional evaluation of extruded complementary foods from blends of fonio(Digitaria Exilis Stapf) and cowpea (Vigna Unguiculata L. Walp) flours (2012)
"Complementary foods were formulated from fonio and cowpea, indigenous cereal and legume grains respectively. Both fonio and cowpea grains were prepared into flours. Blends of 50:50, 60:40 and 70:30 (w/w) fonio and cowpea flours respectively were 'prepared. The blends were conditioned to 22% moisture content (dry basis) by adding calculated distilled water and 5% vegetable oil was thoroughly mixed with each blend. The blends were separately extruded using a single screw extruder at 140 •C barrel temperature. The raw samples and extrudates were evaluated for proximate composition including crude protein, crude fibre, ash, fat, moisture using standard AOAC methods and trypsin inhibition activity using a recognized method. Nutritional quality of the extrudates was determined using rat feeding method. The animals were fed compounded experimental and control diets for 28 days. They were sacrificed after the experiment and their internal organs were removed and weighed. The results observed in this study revealed that blends of fonio and cowpea flours produced good complementary foods in terms of proximate composition especially protein content which increased with increase amount of cowpea in the blends. Protein content of formulated foods were 16.5- 20.3% compared to 7.91%' value for fonio alone. Trypsin inhibition activities were drastically reduced in the extrudates by 81-82% compared to the raw blends used to prepare them, Protein quality evaluation revealed that the extrudates compared favourably with casein diet at 10% isonitrogenous protein level in all attributed studied. The extrudates had high protein quality and can support the growth of infants in developing countries."